The effectiveness of cognitive-behavioral therapy for obsessive-compulsive disorder by using remote digital knowledge media in a sample in my extended family (Al-Jazeera State- Sudan) - Ali, Bakhita Mohammed Zain (Journal of Educational and Psychological Sciences, 2025)
The aim of the study is to examin the effectiveness of cognitive-behavioral therapy for obsessive-compulsive disorder by using remote digital knowledge media. in a sample in the researcher‘s extended family (Al-Jazeera State- Sudan) extended period (Al Jazeera State- Sudan), and to achieve this goal, the researcher used the Quasi experimental approach, on a sample of (11) patients, their ages between (18-25), using the Yale-Brown Obsessive Compulsive Scale for obsessive-compulsive disorder. Through her program directed to the sample individuals who suffer from compulsive behaviors or obsessive thoughts, whether separate or mixed, prepared by the researcher. It was implemented remotely using digital knowledge represented in the media of technology to fulfill the desire of the program participants. The statistical package for social sciences (SPSS) program was used to analyze the data, including the Wilcoxon Yale-Brown scale test to test hypotheses. Where the results of the research were as follows: the cognitive-behavioral therapy program effectively in reduction for obsessive-compulsive disorder of members sample. There are statistically significant differences between the mean scores of the sample individuals, between the pre- and post-measurement, in favor of the post-measurement, in the effectiveness of cognitive-behavioral therapy for obsessive-compulsive disorder by using digital knowledge media remotely in a sample in my extended family (Al-Jazeera State- Sudan). as shown The results also showed that there were no statistically significant differences between the average scores of the respondents in the post-measurement and follow-up, the effectiveness of cognitive-behavioral therapy for obsessive-compulsive disorder through the use of remote digital knowledge media among the members of the current research sample. The research reached a set of recommendations, including: support from the family for girls. Until the recovery from obsessive-compulsive disorder continues.
Keywords: cognitive-behavioral therapy; obsessive-compulsive disorder; distance; digital modes of knowledge